Leaching of rare earth elements from fluorescent powder using the tea fungus Kombucha. (April 2017) - Hopfe, Stefanie; Flemming, Katrin; Lehmann, Falk; Möckel, Robert; Kutschke, Sabine; Pollmann, Katrin
Graphical abstract: Highlights: Leaching of hardly soluble REE-waste with microorganisms is possible. Rare Earth Elements from fluorescent phosphor were leached by Kombucha/-metabolites. Microbial produced organic acids, mainly acetic and gluconic acid contribute to leaching process. Highest leaching results (7.9%)were obtained with spent medium of shaken Kombucha. Leaching with mixed culture is more efficient than single isolates or organic acids. Abstract: In most modern technologies such as flat screens, highly effective magnets and lasers, as well as luminescence phosphors, Rare Earth Elements (REE) are used. Unfortunately no environmentally friendly recycling process exists so far. In comparison to other elements the interaction of microorganisms with REE has been studied to a less extent. However, as REE are ubiquitously present in nature it can be assumed that microorganisms play an important role in the biogeochemistry of REE. This study investigates the potential of organic acid-producing microbes for extracting REE from industrial waste. In Germany, 175 tons of fluorescent phosphor (FP) are collected per year as a distinct fraction from the recycling of compact fluorescent lamps. Because the FP contains about 10% of REE-oxides bound in the so-called triband dyes it is a readily accessible secondary resource of REE. Using the symbiotic mixed culture Kombucha, consisting of yeasts and acetic acid bacteria, REE were leached at a significant rate. The highest leaching-rates were observed in shake cultures using the entire Kombucha-consortium or its supernatant as leaching agent compared to experiments using the isolates Zygosaccharomyces lentus and Komagataeibacter hansenii as leaching organisms. During the cultivation, the pH decreased as a result of organic acid production (mainly acetic and gluconic acid). Thus, the underlying mechanism of the triband dye solubilisation is probably linked to the carboxyl-functionality or a proton excess. In accordance with the higher solubility of REE-oxides compared to REE-phosphates and –aluminates, the red dye Y2 O3 :Eu 2+ containing relatively expensive REE was shown to be preferentially solubilized. These results show that it is possible to dissolve the REE-compounds of FP with the help of microbial processes. Moreover, they provide the basis for the development of an eco-friendly alternative to the currently applied methods that use strong inorganic acids or toxic chemicals.